2014
DOI: 10.1002/jor.22663
|View full text |Cite
|
Sign up to set email alerts
|

Co-cultures of programmable cells of monocytic origin and mesenchymal stem cells do increase osteogenic differentiation

Abstract: Impaired bone healing can occur with numerous pathologic conditions like trauma, osteoporosis, and infection. Therefore tissue-engineering strategies that aim to enhance osteogenic differentiation of stem cells in order to accelerate bone healing are a major goal of contemporary regenerative research. In this study we cultivated mesenchymal stem cells (MSC) together with the recently patented programmable cells of monocytic origin (PCMO) to test whether co-cultures promote an osteogenic differentiation process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In this line, lymphocytes were reported to inhibit MSC-driven bone regeneration through the secretion of IFN-γ and TNF-α ( 57 ). Similarly, mononuclear phagocytes were reported to drive osteogenic differentiation ( 58 , 59 ). No evidence of a direct role of DCs in MSCs differentiation is so far available.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, lymphocytes were reported to inhibit MSC-driven bone regeneration through the secretion of IFN-γ and TNF-α ( 57 ). Similarly, mononuclear phagocytes were reported to drive osteogenic differentiation ( 58 , 59 ). No evidence of a direct role of DCs in MSCs differentiation is so far available.…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of this fact, further studies are necessary to investigate the effect of aging on cocultured aged and young MΦ and cells such as MSCs, to further understand the effects of inflammatory cells on bone formation. Limited studies have been reported on this subject [3740]. Third, although this study was very labor intensive, the experiment was performed only twice and the cells were pooled together.…”
Section: Discussionmentioning
confidence: 99%
“…Different co-culture models for MSCs/osteoblasts and osteoclasts are found in literature [12,14,15,17,20]. One system consists of hMSCs and generated osteoblasts cultured on two levels of membrane-like structures from mineralized collagen.…”
Section: Different Co-culture Set-ups In Comparisonmentioning
confidence: 99%
“…A set-up in which monocytes/osteoclasts and osteoblasts are cultured simultaneously maintains cell-cell interactions and the exchange of soluble factors that are postulated to be essential for the stimulation of osteoclast differentiation [6]. Some studies evaluated the influence of monocytes on the osteogenic differentiation of MSCs [17][18][19][20]. It could be shown that factors such as bone morphogenetic protein 2 are secreted by monocytes that induce an osteogenic lineage commitment of MSCs [19].…”
Section: Introductionmentioning
confidence: 99%